Cysteine Functionalization in the Synthesis of Complex and Well-Defined Bioconjugates - António, João (2020)
Cancer is one of the leading causes of death worldwide and is a major economic burden for governments and health systems. To address this critical health problem and explore a major economic market, ample research has been performed in the development of novel therapies. Antibody-drug conjugates (ADCs) present themselves as clear front-runners in the battle against cancer. By merging the exceptional targeting ability of antibodies and the potency of powerful cytotoxic drugs, ADCs display high levels of selectivity, tolerability and cytotoxic activity. The success of an ADC is closely related with the careful optimization of its four major components: the antibody, the payload, the linker and the bioconjugation technology. The linker, in particular, must be stable in solution, and capable of releasing the payload upon a predetermined stimuli. Boronic acids have been shown to react with oxygen species (ROS) and were widely used as ROS-responsive handles. However, boronic acids display relatively low stability in physiological conditions and promiscuous reactivity with endogenous molecules, such as sugars and proteins. In this work we identified diazaborines as stable alternatives to boronic acids that retain traditional boronic acid reactivity. In our first work, we demonstrated that boronic acids could inhibit selectively Human Neutrophil Elastase (HNE) with low μM potency. HNE is a serine protease present in diverse inflammatory processes and often implicated in tumor progression and for which there is no know inhibitor marketed. After computer-assisted optimization of the scaffold we achieved molecules with IC50 2.7 ± 0.6 μM, which is similar to the activity of boronic acid analogues. Finally, the diazaborines were shown stable over 24 hours in different pHs and plasma, contrarily to boronic acids which displayed half-lives around two hours. After recognizing diazaborine’s stability, we hypothesized it could retain boronic acid’s reactivity towards ROS. Gratifyingly, they are swiftly oxidized in the presence of 10 equivalents of hydrogen peroxide and are able to release a molecular payload. After carefully studying the oxidation mechanism, we used diazaborines to generate bioconjugates with model peptides that were stable in buffer and responsive to hydrogen peroxide. Finally we designed a breast cancer targeting ADC by using a diazaborine linker to attach the cytotoxic drug SN-38 to an engineered trastuzumab. With this work we demonstrated that diazaborines are versatile molecules that could be very useful in designing new scaffolds for medicinal chemistry and chemical biology in the preparation of novel targeted drug conjugates.